2011
DOI: 10.2220/biomedres.32.395
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep bruxism and stress sensitivity in an experimental psychological stress task

Abstract: The objective of this study was to examine the association between sleep bruxism and psychological stress. The subjects consisted of 76 volunteers, who were divided into those with and without bruxism according to the diagnostic criteria for sleep bruxism outlined by the American Academy of Sleep Medicine (AASM). Stress sensitivity was evaluated before and after an experimental stress task, which involved simple mathematical calculations. It was assessed objectively by measuring the subjects' salivary chromogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 25 publications
5
25
1
Order By: Relevance
“…Psychosocial job stress, low social support from supervisors or colleagues and high‐depressive symptoms demonstrated a significantly increased risk of bruxism in a study involving 2680 participants . These findings tend to agree with those of other studies demonstrating a significant association between tooth wear, depression, stress, and emotional stability …”
Section: Tooth Wear and Depressionsupporting
confidence: 87%
“…Psychosocial job stress, low social support from supervisors or colleagues and high‐depressive symptoms demonstrated a significantly increased risk of bruxism in a study involving 2680 participants . These findings tend to agree with those of other studies demonstrating a significant association between tooth wear, depression, stress, and emotional stability …”
Section: Tooth Wear and Depressionsupporting
confidence: 87%
“…The main role in the tension coordination belongs to gamma neurons, which are controlled by higher centers and participate in the development of an abnormal muscle activity (Figure 1) [17]. Chronic stress and warning reactions triggered by it manifest themselves as functional deficiencies of the nervous-muscle system and are the main etiologic factors of psycho-dependent bruxism [41]. When these disturbances appear, attention is drawn by venting the accumulated tensions directly through the dental arches, by means of increased muscle activity, which may lead to headaches.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have evaluate children's behavior and demonstrated that psychological and emotional aspects, such as anxiety, aggressiveness, and hyperactivity, have been associated with possible sleep bruxism. 31,32,33 Recently, this theory has been challenged, since bruxism originates from the central nervous system, so this association would be more related to awake bruxism. Therefore, these results are consistent with those of other studies carried out with adults and children.…”
Section: Discussionmentioning
confidence: 99%